Experimental study of rapid prototyping of manufacturing plastic product using response surface methodology - Syed Mohd Nor Irsyad, Sayed Mohd Nordin (2013)
This study basically shows a detailed study to manufacture Coffee Maker using Rapid prototyping using Response Surface Methodology. Fused deposition modeling (FDM) is a process for developing Rapid Prototyping (RP) objects by depositing fused layers of material according to numerically defined cross sectional geometry. The quality of FDM produced parts is significantly affected by various parameters used in the process. This dissertation work aims to study the effect of three process parameters such as layer thickness, build orientation, and air gap on mechanical property of FDM processed parts. In order to reduce experimental runs, Response Surface Methodology (RSM) based on central composite design (CCD) is adopted. Specimens are prepared for tensile and surface roughness test as per ASTM standards. Empirical relations among responses and process parameters are determined and their validity is proved using analysis of variance (ANOVA). Response surface plots are analyzed to establish main factor effects and their interaction on responses. Optimal factor settings for maximization of each response have been determined. Major reason for weak strength of FDM processed parts may be attributed to distortion within the layer or between the layers while building the parts due to temperature gradient. To this end, mechanical properties like tensile strength and surface roughness finish of the produced parts are considered as multiple responses and simultaneous optimization has been carried out with the help of response optimizer. Coffee Maker parts are manufacture using optimum parameter determines. The Coffee Maker then been assemble and test its function ability.